Pengaruh Bermain Drama terhadap Frekuensi Menggosok Gigi pada Anak Usia Prasekolah di Rumah Sakit - Eka Rokhmiati Wahyu Purnamasari; Indri Sarwilli (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2021)
Play is funnies, any spontaneous and activity provides enjoyment. Play is of vital importance for health development of preschool child. Play offer ample physical, emotional, cognitive and social benefits. The child in hospitalization expressed feelings of anger, fear, insecurity, anxiety, guilt, hopelessness and deep loneliness exacerbated. Personal hygiene is a basic human need. Insufficient brush tooth can affect child`s health (caries). During Hospitalization, a child may be affected by less brush tooth. These Problem sholud be addressed to allow preschool child to get brush tooth twice days. Role play Dramatic Therapy is a nursing intervention, that may be applied to manage less brush tooth. This study aims to determine effect play role in frequency brush tooth in hospital. This study was conducted in preschool children who treated in hospital with 32 samples. The study was conducted in 2 September - 27 September 2019. The study was conducted with quantitative research using category comparison, pre and post test intervention. Result; there was a significant comparison before and after play therapy and frequency brush tooth with 3 days intervention. There was p value 0.007 Role Play Dramatic Therapy in hospital can be implemented on preschool children to increase healty mouth with frequency brush tooth.